1985
DOI: 10.1007/bf02382454
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees' (Pan troglodytes) choice of prey among termites (macrotermitinae) in western Tanzania

Abstract: ABSTRACT. This study examines factors affecting chimpanzees' preying on termites, especially their choice of prey species. Regular surveys of a large sample of termite-mounds in the Mahale Mountains, Tanzania, confirmed that chimpanzees of B Group obtained Macrotermes, which were relatively uncommon, by the use of fishing-tools, but ignored the much more abundant Odontoterrnes. This preference appeared to reflect Macrotermes' more extended swarming period, greater accessibility, larger size, and less noxious t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
3
16
0
1
Order By: Relevance
“…This study revealed that socially housed chimpanzees are sensitive to fluctuations in availability of a preferred food, and the results are consistent with the observation that fluctuations in the availability of food can influence the foraging patterns of chimpanzees living in the wild [Wrangham, 1977;Ghiglieri, 1984;Goodall, 19861. As a group, the subjects that learned the color/food associations responded to the station with oranges with approximately equal frequency when the probability of availability was 1.0 and 0.5, but their frequency of responding decreased significantly when the probability of availability was reduced to 0.1.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that socially housed chimpanzees are sensitive to fluctuations in availability of a preferred food, and the results are consistent with the observation that fluctuations in the availability of food can influence the foraging patterns of chimpanzees living in the wild [Wrangham, 1977;Ghiglieri, 1984;Goodall, 19861. As a group, the subjects that learned the color/food associations responded to the station with oranges with approximately equal frequency when the probability of availability was 1.0 and 0.5, but their frequency of responding decreased significantly when the probability of availability was reduced to 0.1.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, Gombe also shared with Bilenge the presence of compact mounds of Cubitermes N1SHIDA and UEHARA (1980) and confirmed by direct observation in this study (MCGREW & COLLINS, 1985). Conversely, the relative rarity of tool use at Kasoje can be attributed to the rarity or absence of Macrotermes there.…”
Section: Gombesupporting
confidence: 84%
“…Odontotermes were particularly abundant at Bilenge but also present at Kasoje and Gombe. Previous observations suggest that chimpanzees do not eat this genus, and we agree with NISHIDA and UEHARA (1980) that this is probably because they are noxious and unpalatable, although other factors may contribute (COLLINS & MCGREW, 1985).…”
Section: Other Aspects Of Termite Availabilitysupporting
confidence: 83%
See 1 more Smart Citation
“…The pattern and ratio of tooth wear in Mahale chimpanzees (ex ceptMusa) was quite similar to the Gombe chimpanzees (Kilgore, 1989). And this likeness seems to be influenced by the similarity in biotic and abiotic factors at the two sites (Collins and McGrew, 1985). Conversely, Musa's dental wear stage was lower, especially on posterior teeth, than the wear stage in Gombe specimens of the same generation (i.e.…”
Section: Discussionmentioning
confidence: 76%